2014
DOI: 10.1016/j.jvs.2014.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of red blood cell omega-3 fatty acid content in male veterans with peripheral arterial disease

Abstract: Objectives Despite available medical therapies, patients with peripheral arterial disease (PAD) remain at high risk for cardiovascular events. n-3 polyunsaturated fatty acids (PUFA), derived from marine sources, have been shown to improve cardiovascular mortality. The omega-3 index (O3I), a proportion of the n-3 PUFA eicosapentaenoic acid and docosahexaenoic acid in the red blood cell membrane, correlates with cardiovascular risk. Previous investigations have found that n-3 PUFA supplementation, fish consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…A higher omega‐3 index is associated with older age, increasing body mass index, and a history of smoking and fish oil intake in patients with peripheral artery disease (Nosova et al. ). RBC n −6 fatty acids have been found to be positively associated, and RBC n −3 fatty acids are inversely associated with body weight gain (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…A higher omega‐3 index is associated with older age, increasing body mass index, and a history of smoking and fish oil intake in patients with peripheral artery disease (Nosova et al. ). RBC n −6 fatty acids have been found to be positively associated, and RBC n −3 fatty acids are inversely associated with body weight gain (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unknown whether supplementation of n‐3 PUFAs could reduce neointimal hyperplasia after vascular intervention or surgery. It is noteworthy that recent studies suggest that short‐term high‐dose nutritional supplementation with fish oil can alter the lipid metabolome in subjects with peripheral artery disease, suggesting the basis for further interventional trials in this population (46). In summary, our study demonstrates that systemic administration of 2 DHA‐derived SPMs (RvD2 and MaR1) attenuates low flow‐induced arterial remodeling in mice, likely via effects on leukocyte trafficking, macrophage, and VSMC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…n-3 PUFAs derived from fish oil have been found to yield beneficial effects on cardiovascular health (25, 26), including decreasing mortality from cardiovascular causes, all-cause mortality, and non-fatal cardiovascular events (2730). Our previous work has shown that predictors of higher omega-3 index in patients with PAD were older age, elevated BMI and prior fish oil supplementation (12). Here we investigated the predictors of a response to fish oil supplementation and found that a lower BMI and higher LDL cholesterol were the only independent predictors of a favorable response in the omega-3 index.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that in patients with PAD, a higher omega-3 index was associated with older age, elevated body mass index (BMI), and prior fish oil supplementation, while a history of smoking correlated with a lower omega-3 index (12). We also demonstrated the ability of high-dose, short duration n-3 PUFA supplementation to increase the omega-3 index in patients with PAD (13).…”
Section: Introductionmentioning
confidence: 99%